Bioelectronic Approaches to Control Neuroimmune Interactions in Acute Kidney Injury - Inoue, Tsuyoshi (Cold Spring Harb Perspect Med, 2019)
Recent studies have shown renal protective effects of bioelectric approaches, including ultrasound treatment, electrical vagus nerve stimulation, and optogenetic brainstem C1 neuron stimulation. The renal protection acquired by all three modalities was lost in splenectomized mice and/or α7 subunit of the nicotinic acetylcholine receptor–deficient mice. C1 neuron-mediated renal protection was blocked by β2-adrenergic receptor antagonist. These findings indicate that all three methods commonly, at least partially, activate the cholinergic anti-inflammatory pathway, a well-studied neuroimmune pathway. In this article, we summarize the current understanding of neuroimmune axis-mediated kidney protection in preclinical models of acute kidney injury by these three modalities. Examination of the differences among these three modalities might lead to a further elucidation of the neuroimmune axis involved in renal protection and is of interest for developing new therapeutic approaches.